Optimization of Catfish (Clarias sp.) Based Amplang Formulation: Physicochemical, Texture, and Sensory Quality Evaluation - Noviansyah, Novan; Lestari, Juniarti Wulan (Universitas Kristen Cipta Wacana, 2025)
The diversification of freshwater fish products, particularly catfish (Clarias sp.), into value-added snacks like amplang represents a crucial strategy to enhance economic resilience for small-scale farmers in Indonesia facing price volatility. This study aimed to optimize the formulation of catfish-based amplang by varying the proportions of catfish meat, tapioca flour, and egg white to achieve optimal physicochemical characteristics, texture, and sensory acceptance. The research employed a factorial Completely Randomized Design (CRD) with nine treatment combinations: fish meat (80 g, 100 g, 120 g), tapioca flour (60 g, 75 g, 90 g), and egg white (30%, 40%, 50% w/w of dough). Evaluated parameters included moisture, protein, fat, ash, and carbohydrate content, as well as expansion ratio, fracture force, and hedonic scores (color, aroma, taste, texture). Statistical analysis was conducted using ANOVA followed by Duncan's Multiple Range Test (DMRT). The optimal formulation (100 g fish meat, 75 g tapioca, and 40% egg white) yielded a product with superior characteristics: 3.40% moisture, 17.86% protein, 4.66% fat, 2.35% ash, a 666.67% expansion ratio, and the highest overall acceptability (4.6/5). The optimal product complies with the SNI 7762:2013 quality standard and offers a viable model for Small and Medium Enterprises (SMEs) to increase the market value of aquaculture commodities.